Assessing waivered and non-waivered physician barriers to treating patients with substance use disorders: a cross-sectional Kentucky pilot. Issue 4 (3rd October 2022) - Thompson, Robin A.; Johnson, David; Kizewski, Amber L.; Baier, Lori; Coburn, Karen; White, Jennifer; Bunn, Terry; Fletcher, Ernest L.
Abstract: Introduction: Opioid and other substance use disorders (OUD/SUDs) have been and continue to be significant public health issues. The standard of care for OUD is the use of medication for opioid use disorder (MOUD) in conjunction with counseling or behavioral therapies, yet research has indicated that barriers exist for patients accessing MOUD as well as for physicians prescribing MOUD due to requirements associated with the DATA 2000 waiver. Methods: A pilot cross-sectional survey was conducted among Kentucky physicians in order to reassess common barriers as well as to explore barriers that non-waivered providers face to becoming waivered. Barriers were compared by waiver status (waiver vs. non-waivered) as well as geographic location (rural vs. non-rural). Results: Compared to waivered physicians, non-waivered physicians were significantly less likely to report positive personal beliefs related to the use of MOUD for OUD and reported significantly more barriers to treating OUD patients in the areas of physicians' practice and culture, auditing, and institutional support and resources ( p < .05). The majority (69%) of all physicians indicated they would benefit from a tool kit with evidence-based clinical guidelines. Conclusions: The barriers and beliefs identified in this pilot study indicate the need for policy action at the federal level to reduce barriers and incentivize more physicians to obtain waivers to treat OUD. Further, the development of brief educational resources tailored to physicians to treat OUD patients including pregnant patients with OUD is recommended.